A general equilibrium analysis of protection : the effects of protection in Australia - Evans, David (Amsterdam : North-Holland Pub. Co., 1972)
This book describes a technical exercise in quantitative economics which does not question the political assumptions which underly the study.
Bibliography: p. 207-212.
osc 12/07/2018
Loans
Keywords: Tariff